Mahabbah Al-Ghozali as a Model of Education and Child Care - Husna, Hilyatul; Wasik, Abdul (Edukasi: Journal of Educational Research, 2021)
This journal is a library research entitled "The Concept of Muhasabah Al-Ghazali as a Method of Parenting Patterns". This research will discuss what are the things related to muhasabah and parenting, and how the concept of alghazali becomes a method for parenting. The research data were obtained from the translation book Ihya 'Ulumuddin as the main source and supported by books, translated books, and other literature that discusses parenting and muhasabah. This research is then analyzed using descriptive analytical techniques. Al-Ghozali understands that nurture is a form of knowledge transfer and is a way to spread kindness, elevate human dignity, and instill human values ​​with the concept of muhasabah through several methods, namely exemplary methods, habituation methods, advice methods, and reward and punishment methods. and exemplary methods with the stages of takhalli, tahalli, and tajalli in the form of mahdah and ghairu mahdah worship practices such as fasting, prayer, remembrance, and prayer. Therefore, to shape children into individuals with noble characters and be able to carry out duties as khalifa fil ardh, parenting by applying the muhasabah method should be carried out since the pre-natal period and continues until the post-natal period.